The Influence of Leadership Style, Motivation and Work Discipline on Employee Performance - Nur Aeni; Heri Gatot Kuswanto (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2021)
The purpose of this study was to determine the magnitude of the influence between Leadership Style, Motivation, and Work Discipline on Employee Performance. Leadership style is one of the ways a leader influences, directs, and controls the behavior of others to achieve a goal. Motivation is a condition that drives employees who are directed to achieve organizational goals, mental attitude is a mental condition that encourages employees to strive to achieve maximum work performance. Work Discipline is a disciplined attitude that must be obeyed by all employees to achieve a goal set by the company. Employee performance is a work result that can be achieved by a person or group of people in an organization according to their authority and responsibility to achieve organizational goals. The number of samples in this study was 82 employees of PT HTSI. The sampling method used was nonprobability sampling, namely the saturated sampling method with the tool of SPSS statistical software. The results of this study prove that there is a positive and significant influence between leadership style and employee performance, there is a negative and significant influence between motivation and employee performance, there is a positive and significant influence between work discipline and employee performance.